Assessment of prognostic ability of intracerebral hemorrhage score with special reference to a tribal population - Amanul Haque,; Sanjay Sarkar,; Seema Mondal,; Ruplekha Mitra Mustaphi, (Asian Journal of Medical Sciences, 2023)
Background: Stroke is the second leading cause of death worldwide. Intracerebral hemorrhage (ICH) accounts for 10% of all strokes, and about 35–45% of patients die within the 1st month. The scarcity of robust data on the validity and utility of the ICH score on the Indian population in a resource-poor health facility is a compelling factor for more study in this field, especially among the tribal population in this region. ICH score is a simple, easy-to-calculate prognostic indicator of hemorrhagic score. Aims and Objectives: The aim of this study is to estimate the prognostic significance of ICH score (both modified and the original) in hemorrhagic stroke in terms of mortality and morbidity and to analyze associated risk factors like mortality, morbidity, and motor recovery of hemorrhagic stroke in tribal and non-tribal population. Materials and Methods: The study was institution-based observational and prospective study of 120 new-onset hemorrhagic stroke cases diagnosed by clinical and radiological evaluation admitted in this medical college during the period of study. Along with history, clinical examination and CT scan brain guided ICH scoring is done, follow-up at the end of 1 week and at the 5th week including physical performance assessment and reviewing of records and certificates. P<0.05 was considered statistically significant. Results: The patients with modified ICH score 0 had 100% improvement whereas the improvement was seen in 54.84% of patients with scores 1 and 2. A total 50% of patients with scores 3 and 4 improved significantly. The incidence of hypertension was more in non-tribal population (70.45%) than total tribal population (56.25%) of study and Compared to non-tribal population (23.86%), tribals had more history of addiction (40.63%). Conclusion: Both the ICH Scores, modified and the original, were practical and valid predicting mortality in our setup. However, the modified one was more accurate and pragmatic in our study.